Band Gap Engineering of Wurtzite Silicon by Uniaxial Pressure (International Journal of Innovative Research in Computer Science & Technology, 2024)
Electronic properties of wurtzite silicon  (WZ-Si) are investigated by first-principle calculation. It is  found that WZ-Si is an indirect band-gap semiconductor at  ambient condition. A uniaxial strain along the c-direction can  reduce the direct energy gap at Γ significantly. Calculated  pressure needed to compress WZ-Si is not too high, which  shows strained WZ-Si would be potential in practical use.  The effective mass of electron is found strongly dependent on  strain which could be used to tailor the transport properties.
Keywords: Electronic properties; Wurtzite silicon; Uniaxial pressure